Organs Blood Flow during Elevation of Body Temperature in Sevoflurane Anesthetized Rats - Koichi Shimo; Ko Takakura; Kenji Shigemi (Anesthesiology Research and Practice)
The aim of this study is to investigate how elevation of body temperature changes organs blood flow during sevoflurane anesthesia. We conducted in vivo research on 14 male Wistar rats to monitor pulse rate and arterial blood pressure and measure hepatic, small intestinal, renal, and descending aortic blood flow using a laser Doppler blood flowmeter. We assessed the changes in organ blood flow, pulse rate, and arterial blood pressure during elevation of the rats’ body temperatures up to 41.5°C under anesthesia with 2.0% or 3.0% sevoflurane. We concluded that elevation of body temperature up to 39.5°C does not change hepatic, small intestinal, and renal blood flow during 2.0 and 3.0% sevoflurane anesthesia.